2020
DOI: 10.1111/ecog.05015
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of tundra encroachment by trees and tall shrubs in the western Brooks Range of Alaska

Abstract: Climate change is expected to increase woody vegetation abundance in the Arctic, yet the magnitude, spatial pattern and pathways of change remain uncertain. We compared historical orthophotos photos (1952 and 1979) with high-resolution satellite imagery (2015) to examine six decades of change in abundance of white spruce Picea glauca and tall shrubs (Salix spp., Alnus spp.) near the Agashashok River in northwest Alaska. We established ~3000 random points within our ~5500 ha study area for classification into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
(49 reference statements)
4
18
0
Order By: Relevance
“…Our data show that shrub encroachment in the European Alps has been occurring through a previously undescribed successional pathway involving pioneer hygrophilous Salix shrubs that are able to colonize both climax and pioneer vegetation across different elevation belts up to 3000 m a.s.l. This pathway is similar to processes reported in sub-Arctic and Arctic regions (Tape et al 2006, Forbes et al 2010, Myers-Smith et al 2011, Jørgensen et al 2013, Rinas et al 2017, Myers-Smith and Hik 2018, Terskaia et al 2020), but has not been reported previously in the Alps, where shrub encroachment has previously been reported involving late successional species typical of climax subalpine shrub vegetation (Dullinger et al 2003, Cannone et al 2007, Stöckli et al 2011, Cannone and Pignatti 2014, Francon et al 2020, Malfasi and Cannone 2020. The successful encroachment of these Salix shrubs initiated more recently (late 1950s) than did that of late successional species (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Our data show that shrub encroachment in the European Alps has been occurring through a previously undescribed successional pathway involving pioneer hygrophilous Salix shrubs that are able to colonize both climax and pioneer vegetation across different elevation belts up to 3000 m a.s.l. This pathway is similar to processes reported in sub-Arctic and Arctic regions (Tape et al 2006, Forbes et al 2010, Myers-Smith et al 2011, Jørgensen et al 2013, Rinas et al 2017, Myers-Smith and Hik 2018, Terskaia et al 2020), but has not been reported previously in the Alps, where shrub encroachment has previously been reported involving late successional species typical of climax subalpine shrub vegetation (Dullinger et al 2003, Cannone et al 2007, Stöckli et al 2011, Cannone and Pignatti 2014, Francon et al 2020, Malfasi and Cannone 2020. The successful encroachment of these Salix shrubs initiated more recently (late 1950s) than did that of late successional species (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…To minimize the spatial errors, we resampled 30-m data to 90 m and generalized the land cover classes from more specific ones [ 50 ]. Third, the SnowModel results can often be improved with model training data, however, weather data (e.g., snow depth and air temperature) at high elevation sites within the North and South regions in LCNPP were limited ( S1 Text ), which is a common challenge in arctic and subarctic environments [ 77 ]. Inclusion of data from additional weather stations would help improve estimates of the climate variables.…”
Section: Discussionmentioning
confidence: 99%
“…Arctic and subarctic regions are rapidly warming, which is leading to northward and altitudinal range expansion of shrubs and trees (Myers‐Smith et al, 2019; Tape et al, 2012; Terskaia et al, 2020). Although this ‘shrubification’ likely contributes to higher primary production (Zhang et al, 2014), it could also accelerate fungal‐driven soil organic matter (OM) decomposition and result in a large net loss of ecosystem carbon and exacerbate climate change (Hartley et al, 2012; Parker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%